Jamun – at a glance - Rajan, S. (Indian Horticulture, 2019)
Jamun cultivation can be introduced in arid and semi-arid, resource-poor and wasteland areas where other crops are difficult to grow. It is a good source of minerals, sugar, proteins, iron and other nutraceuticals. It requires dry weather at the time of flowering and fruit setting. In sub-tropical areas, early rain is beneficial for proper development of fruit size, colour, maturity and taste.